Interaction of an intense few-cycle infrared laser pulse with an ultrathin transparent liquid sheet - Ferchaud,C; Jarosch,S; Avni,T; Alexander,O; Barnard,J; Larsen,E; Matthews,M; Marangos,J (Optics Express, 2022)
We experimentally study the interaction between intense infrared few-cycle laser pulses and an ultrathin (∼2 µm) flat liquid sheet of isopropanol running in vacuum. We observe a rapid decline in transmission above a critical peak intensity of 50 TW/cm2 of the initially transparent liquid sheet, and the emission of a plume of material. We find both events are due to the creation of a surface plasma and are similar to processes observed in dielectric solids. After calculating the electron density for different laser peak intensities, we find an electron scattering rate of 0.3 fs-1 in liquid isopropanol to be consistent with our data. We study the dynamics of the plasma plume to find the expansion velocity of the plume front.